German Planning Discourses on the Post-Pandemic City. - Krüger, Arvid (Taylor & Francis, 2020)
The pandemic has altered the way we live and it is difficult to foresee which alterations will sustainably change the way our towns and cities function. Some alterations are rooted in the changes of 2020; others have been boosted by the pandemic. This article gives an overview of a planners’ debate in German publications in newspapers and practice-oriented journals during 2020. If published in scientific journals, some may have been considered preprints and/or opinion articles. The aim of this article is to contextualise these German-language contributions to a societal discussion – together with my observations as somebody who is, at the same time, a user and a professional observer of the city – into an emerging scientific discourse. It focuses on urban retail, the question of urban solidarity and gives a scenario-like outlook on the German small town and the German big city, which stand for the polycentrism of Germany and Central Europe and for major types of German and European urban forms (small and medium-sized towns: 20 000–100 000 inhabitants; big cities: 100000–500000 inhabitants). It concludes with procedural options for planners that derive from everyday practice and scientific discourses on German Urban Renewal.
Keywords: Stadtplanung; Großstadt; Kleinstadt; Zukunftsperspektive; Einkaufsverhalten; Einzelhandel; Innenstadtentwicklung; Stadterneuerung; Corona-Krise